Effect of Aloe Vera Gel Extract on C-Reactive Protein Variations Induced by Methotrexate in Albino Rats - Al-Huchimi, Esraa Mohammed Kadhim; Ridha, Ameer Mohammed; Al-Ardawi, Hassan Falih Hassan Salman (Medical Science Journal for Advance Research, 2024)
Background: The present research attempts to investigate the efficiency of the gel form of aloe Vera against side effects that are induced by the effecting of the drug Methotrexate in adult Albino rats with highly sensitive C-reactive protein and provide protection and treatment from this deficiency, if drugs are taken alone or in combination in cases where require it, Group 1: control, Group2: Methotrexate 1mg/kg Group3: give gel of Aloe Vera 250 mg/ kg, Group4: give gel of Aloe Vera 500 mg/ kg,, Group5: MTX 1 mg /kg with 250 mg/kg, Group6: MTX 1 mg/ kg with 500 mg/kg. Samples of blood were taken from every animal after the finish of the three-week study. The results indicated a significant reduction in highly sensitive C-reactive protein In adult Albino rats, animal groups orally received 250 mg /kg of Aloe Vera gel and 500 mg / kg of Aloe Vera gel . High-sensitive C-reactive protein was increased in the group of rats treated with Methotrexate 1 mg /kg, and sensitive C-reactive protein was lower compared with the MTX, groups received MTX 1 mg/ kg together with 250 mg /kg and in groups that received MTX 1 mg /kg together with 500 mg /kg. Conclusion: Based on the study's findings, we deduce that aloe vera gel extract, at varying dosages, can eliminate and lessen adverse effects in rats receiving methotrexate when looking at C_ Reactive Protein.